Mechanism(s) of action underlying the gastroprotective effect of ethyl acetate fraction obtained from the crude methanolic leaves extract of Muntingia calabura - Zakaria, Zainul Amiruddin; Balan, Tavamani; Azemi, Ahmad Khusairi; Omar, Maizatul Hasyima; Mohtarrudin, Norhafizah; Ahmad, Zuraini; Abdullah, Muhammad Nazrul Hakim; Mohd Desa, Mohd Nasir; Teh, Lay Kek; Salleh, Mohd Zaki (BioMed Central, 2016)
Background: Muntingia calabura L. (family Muntingiaceae), commonly known as Jamaican cherry or kerukup siam in Malaysia, is used traditionally to treat various ailments. The aim of this study is to elucidate the possible underlying gastroprotective mechanisms of ethyl acetate fraction (EAF) of Muntingia calabura methanolic leaves extract (MEMC). Methods: MEMC and its fractions were subjected to HPLC analysis to identify and quantify the presence of its phyto-constituents. The mechanism of gastroptotection of EAF was further investigated using pylorus ligation-induced gastric lesion rat model (100, 250, and 500 mg/kg). Macroscopic analysis of the stomach, evaluation of gastric content parameters such as volume, pH, free and total acidity, protein estimation, and quantification of mucus were carried out. The participation of nitric oxide (NO) and sulfhydryl (SH) compounds was evaluated and the superoxide dismutase (SOD), gluthathione (GSH), catalase (CAT), malondialdehyde (MDA), prostaglandin E2 (PGE2) and NO level in the ethanol induced stomach tissue homogenate was determined. Results: HPLC analysis confirmed the presence of quercetin and gallic acid in EAF. In pylorus-ligation model, EAF significantly (p <0.001) prevent gastric lesion formation. Volume of gastric content and total protein content reduced significantly (p < 0.01 and p < 0.05, respectively), while free and total acidity reduced in the doses of 250 and 500 mg/kg (p <0.001 and p <0.05, respectively). EAF also augmented the mucus content significantly (p < 0.001). Pre-treatment with N-nitro-L-arginine methyl ester (L-NAME) or N-ethylmaleimide (NEM) reversed the gastroprotective activity of EAF. EAF treatment markedly ameliorated the SOD, GSH and CAT activity and PGE2 and NO level while attenuating MDA level, relative to the vehicle group. Conclusions: In conclusion, the underlying gastroprotective mechanisms of EAF could be associated with the antisecretory, participation of mucus, antiperoxidative, improvement of antioxidant status, modulation of NO and SH compounds, stimulation of PGE2 as well as presence of quercetin and gallic acid.